2022
DOI: 10.11609/jott.7992.14.7.21473-21475
|View full text |Cite
|
Sign up to set email alerts
|

First Asian record of Light-mantled Albatross Phoebetria palpebrata (Foster, 1785) from Rameswaram Island, Tamil Nadu, India

Abstract: This document is a first sighting record of the Light-mantled Albatross Pheobetria palpebrate from Rameswaram island in Southern India. This is an unusual record from the region as it has not previously been recorded from either South Asia or the Oriental region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…We also recorded 32 sighting records of the N. percnopterus over three years. Prakash et al (2007; reported that N. percnopterus was recorded at the lowest levels in all road transect surveys, and this is a general trend throughout the NBR and the state of Tamil Nadu (Byju, Raveendran 2022).…”
Section: Neophron Percnopterusmentioning
confidence: 92%
“…We also recorded 32 sighting records of the N. percnopterus over three years. Prakash et al (2007; reported that N. percnopterus was recorded at the lowest levels in all road transect surveys, and this is a general trend throughout the NBR and the state of Tamil Nadu (Byju, Raveendran 2022).…”
Section: Neophron Percnopterusmentioning
confidence: 92%
“…Bird survey data provide useful insights for basic and applied ecology, as well as for identifying priority conservation areas (Daniels et al 1991;Peterson et al 2000). Some of the recently published records from this district include sighting of Artic Skua Stercorarius parasiticus (Byju & Raveendran 2022a), and the first Asian record of Light-mantled Albatross Phoebetria palpebrata (Byju & Raveendran 2022b). Previous findings highlight the importance of this area, and prompted us to undertake a baseline survey based on a need for monitoring in new areas in the rapidly changing landscape.…”
Section: Introductionmentioning
confidence: 99%